Black Rot of Crucifers - Tom Kucharek; Jim Strandberg; Amanda Gevens (EDIS)
Revised! PP-13, a 3-page fact sheet by Tom Kucharek, Jim Strandberg, and Amanda Gevens, describes this bacterial plant disease affecting cruciferous vegetables and weeds — its causes and symptoms, and control measures. Published by the UF Department of Plant Pathology, September 2008.